2011
DOI: 10.1017/s000711451000588x
|View full text |Cite
|
Sign up to set email alerts
|

Effect oftrans-fat, fructose and monosodium glutamate feeding on feline weight gain, adiposity, insulin sensitivity, adipokine and lipid profile

Abstract: The incidence of obesity and type 2 diabetes mellitus (T2DM) is increasing, and new experimental models are required to investigate the diverse aspects of these polygenic diseases, which are intimately linked in terms of aetiology. Feline T2DM has been shown to closely resemble human T2DM in terms of its clinical, pathological and physiological features. Our aim was to develop a feline model of diet-induced weight gain, adiposity and metabolic deregulation, and to examine correlates of weight and body fat chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 56 publications
0
20
0
1
Order By: Relevance
“…Given the fact that maternal oral administration of MSG can result in detectable levels of glutamic acid accumulation in the fetal brain (Hermanussen and Tresguerres 2003;Nemeroff et al 1978), and that in rodents, the hepatotoxic effects of MSG may also be apparent even when administered orally (Yu et al 1997), it would be of interest to ascertain the effects of neonatal administration of dietary MSG in a higher animal model. It has previously been shown that intravenous injections of MSG promote the development of hypothalamic lesions in young cats (Tanaka et al 1983); and we have previously shown that whereas neonatal exposure to MSG promotes a phenotype of increased feline adiposity and reduced insulin sensitivity, Trans-fat and HFCS feeding results in an apparent elevation in cortisol and markers of liver dysfunction (Collison et al 2011). The present study seeks to further investigate the effect of Trans-fat, HFCS, and/or MSG on feline hepatic steatosis and gene expression.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…Given the fact that maternal oral administration of MSG can result in detectable levels of glutamic acid accumulation in the fetal brain (Hermanussen and Tresguerres 2003;Nemeroff et al 1978), and that in rodents, the hepatotoxic effects of MSG may also be apparent even when administered orally (Yu et al 1997), it would be of interest to ascertain the effects of neonatal administration of dietary MSG in a higher animal model. It has previously been shown that intravenous injections of MSG promote the development of hypothalamic lesions in young cats (Tanaka et al 1983); and we have previously shown that whereas neonatal exposure to MSG promotes a phenotype of increased feline adiposity and reduced insulin sensitivity, Trans-fat and HFCS feeding results in an apparent elevation in cortisol and markers of liver dysfunction (Collison et al 2011). The present study seeks to further investigate the effect of Trans-fat, HFCS, and/or MSG on feline hepatic steatosis and gene expression.…”
mentioning
confidence: 79%
“…A total of 8 female domestic cats were used to breed the 18 male subjects used in this study, as previously described (Collison et al 2011). Briefly, heating and cooling were electronically controlled and were set to maintain the room in a temperature range from 18 to 25°C.…”
Section: Animals and Dietsmentioning
confidence: 99%
See 3 more Smart Citations